Earth story forces that shape our planet [motion picture] ([United Kingdom] BBC World Wide Limited, 2005)
Unravel the secrets of our planet. Using a combination of breathtaking images of natural world and state-of-the-art graphics, this astonishing series takes us to locations all over the world. From the bottom of the Atlantic Ocean to the Polar ice-cap; into the crater of an active volcano and up to the highest peaks of the Himalayas, Earth Story follows the scientist as they piece together the clues that reveal the serets of our planet and the life it sustains.
Contents: Episode 1: The Time Travellers (50 mins). Episode 2: The Deep. Episode 3: Ring of Fire. Episode 4: Journey to the Center of the Earth. Episode 5: The Roof of the World. Episode 6: The Big Freeze. Episode 7: The Living Earth. Episode 8: Other Worlds
Dolby digital soundtracks contain up to 5.1 channels of discrete audio. Dolby sorround soundtracks contain up to 4 channels of encoded audio. Playback from 2-channel dvd output is compatible with stereo and Dolby Pro Logic.
DD Knowledge
Keywords: Atlantic Ocean; Volcanoes; Polar Ice-Cap.; Earth